An investigation on the effects of the angles between the mitral and aortic orifice during diastolic period using FSI. Issue 3 (September 2017) - Arefin, Md. Shamsul
Abstract: Background: It was well documented that the changes in the physiological structure of the heart can alter the hemodynamic behaviour of the human left ventricle. Although there were various imaging tools that can stipulate the blood flow characteristics inside the ventricle, but the effect of the variation in the angles between the mitral and aortic orifices were yet to be determined. Hence the primary focus of this paper was to use Fluid-Structure Interaction scheme throughout the diastolic phase to examine and determine the hemodynamic behaviour inside the cavity under various angles between the mitral and aortic orifices (50°, 55° and 60°). Methods: The incompressible Newtonian liquid (time dependent), linear viscous liquid and stress tensor equations were combined together with the Navier-Stoke's equations and Arbitrary Lagrangian Eulerian and for the elasticity of the structure. Results: During diastasis, the position of the vortex was seen to be slightly upwards (55°) compared to 50° and 60°. Also, the influence of the wall shear stress was primarily observed to be much higher with the rise in the inlet velocity but the effect was seen reduced when the inlet velocity was minimal. Moreover, at the end of the filling phase maximum intraventricular pressure was obtained to be at the tip of LV for 50° compared to 55° and 60°. Conclusion: These findings provide significant insights on hemodynamic conditions and structural displacement, which from a clinical point of view would be useful in determining different conditions of cardiac diseases.